Functional midterm follow-up comparison of stemless total shoulder prostheses versus conventional stemmed anatomic shoulder prostheses using a 3D-motion-analysis - Spranz, David Maximilian; Wolf, Sebastian Immanuel; Zeifang, Felix; Maier, Michael Wolfgang (BMC musculoskeletal disorders, 2017)
The aim of this study is to compare the functional midterm outcome of stemless shoulder prostheses with standard anatomical stemmed shoulder prostheses and to show that the STEMLESS results are comparable to the STEMMED with respect to active maximum range of shoulder motion (ROM) and Constant score (CS).